(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate overall survival in patients with lung cancer with brain metastasis. Our other aim was to investigate prognostic value of the maximum standardized uptake value (SUVmax) of primary tumor on 18Fluorine-fluorodeoxyglucose positron emission tomography / computed tomography (18F-FDG PET / CT) FDG PET / CT and other clinicopathological parameters. Material and Methods: Fifty-eight patients with lung cancer who underwent for oncologic purpose and had metastatic lesions in the brain were included in the study. The location of the primary lung mass and whether other organ metastases presence was evaluated on the 18F-FDG PET / CT. In axial images, the volume of interest (VOI) was plotted semi-automatically to include lung tumor tissue and SUVmax of the primary lung tumor was measured. Survival analyzes were performed with Kaplan-Meier survival analysis. The prognostic value of the parameters was evaluated using Cox regression analysis.Results: Of the 58 patients included in the study, 6 (10%) were female and 52 (90%) were male. The mean age was 64.8 ± 9.5 years. The mean SUVmax of primary tumor was 10.4 ± 4.5. Median survival was 7 months. Patient age and localization of the primary tumor were prognostic factors for survival in univariate analysis, whereas sex, SUVmax of primary tumor, presence of distant metastasis outside the brain, histologic subtype, surgical status of the metastatic brain mass and treatment type were not. Overall survival was lower in patients with primary tumor located in the left lung than in the right lung.Conclusion: In conclusion, age and localization of primary tumor are prognostic factors, whereas SUVmax of primary tumor does not appear to be a prognostic factor in lung cancer patients with brain metastases.